(untitled) (Diametros, 2012)
The aim of this paper is to analyze the arguments that proponents of the conservative view on the moral status of the human embryo offer in support of their position. I claim that there exists an argument in favour of the conservative position that has been overlooked by virtually all contemporary bioethicists. It refers not to the metaphysical presumptions about the status of the embryo or its developmental capabilities but rather it is based on the criteria of rational decisions under normative uncertainty. I will demonstrate that this argument, although much stronger than many other arguments in support of the conservative view, has very limited use. My analysis will concentrate on the moral status of the early embryo (until about the 14th day of conception) and therefore will be especially important in the context of recent debates about the moral and legal permissibility of research on human embryonic stem cells.